2008
DOI: 10.1016/j.jacc.2007.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Omeprazole on the Antiplatelet Action of Clopidogrel Associated With Aspirin

Abstract: Omeprazole significantly decreased clopidogrel inhibitory effect on platelet P2Y12 as assessed by VASP phosphorylation test. Aspirin-clopidogrel antiplatelet dual therapy is widely prescribed worldwide, with PPIs frequently associated to prevent gastrointestinal bleeding. The clinical impact of these results remains uncertain but merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
347
1
26

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 886 publications
(388 citation statements)
references
References 22 publications
14
347
1
26
Order By: Relevance
“…12 However, the current position of the AHA is that there is no conclusive evidence that this translates to an increased risk of clinically significant thrombosis. 13 Strategies suggested to minimize PPI-induced inhibition include substituting the less inhibitory pantoprazole for omeprazole, 14 and spacing clopidogrel and PPI doses 12 hours apart from each other.…”
Section: Interactionsmentioning
confidence: 99%
“…12 However, the current position of the AHA is that there is no conclusive evidence that this translates to an increased risk of clinically significant thrombosis. 13 Strategies suggested to minimize PPI-induced inhibition include substituting the less inhibitory pantoprazole for omeprazole, 14 and spacing clopidogrel and PPI doses 12 hours apart from each other.…”
Section: Interactionsmentioning
confidence: 99%
“…Gilard et al [7] first highlighted the negative impact of PPIs and, in particular, omeprazole on the pharmacodynamic clopidogrel response, possibly owing to inhibition of CYP2C19, and this group further confirmed this drug-drug interaction by carrying out the randomized and double-blinded Omeprazole CLopidogrel Aspirin study [8]. Since then, however, other groups have shown that this response may not be relevant to all PPIs.…”
mentioning
confidence: 97%
“…Previous studies assessing the pharmacodynamic effects of PPIs on clopidogrel activity have used vasodilator-stimulated phosphoprotein phosphorylation analysis or light-transmittance aggregometry [5,8,16]. To our knowledge, we are the first group to describe this response using the VerifyNow analyzer, a simple near patient device that can be used by clinicians who are not affiliated with academic research centers specializing in platelet function.…”
mentioning
confidence: 99%
“…This hypothesized impairment was additionally supported by the finding of genetic polymorphisms associated in CYP2C19 activity Singh et al 2010;Tiroch et al, 2010) and with a reduced antiplatelet activity and a worse clinical outcome (CV adverse events and re-infarction). Early clinical prospective studies in humans demonstrated a negative effect of omeprazole on surrogate clinical endpoints (ex vivo platelet assay, vasodilatator-stimulated phosphoprotein VASP) while other PPIs (pantoprazole and esomeprazole) did not (Gilard et al, 2008;Cuisset et al, 2009;O'Donoghue et al, 2009;Siller-Matula et al, 2009). …”
Section: Gastroprotective Strategies In Patients Receiving Clopidogrelmentioning
confidence: 99%